Challenging beauty standards: A critical discourse analysis of the Vaseline advertisement on the VaselineID YouTube channel - Safira, Rahmalia Putri; Abrian, Risky (Jurnal Penelitian Humaniora, 2025)
Every woman wants to be beautiful, with fair skin and a proportional body, as per societal standards. However, the existence of beauty standards makes women forget the true meaning of the word 'beautiful' itself. This research aims to reveal and describe the resistance made by young women in the Vaseline advertisement titled "Minder Dikomentarin Orang Karena Kulitmu? Tonton Ini Dulu!" on the VaselineID YouTube account against beauty standards in Indonesia. A qualitative descriptive method helps the researcher analyze the state, message, and meaning present in the advertisement. The critical discourse analysis theory by Sara Mills focuses on feminist discourse and how women are discriminated against in the Vaseline advertisement video. The results of this study show that self-love is essential, especially for women. Societal beauty standards often cause women to lack self-confidence and feel ungrateful for their strengths and weaknesses. Therefore, women should be free to express themselves and be given the opportunity to pursue their dreams without worrying about the judgments and comments of others.